Evaluation of the Effectiveness of In-Service Training Based on the Kirkpatrick Model: A Case Study of a Cardiopulmonary Resuscitation (CPR) Course for Nurses in Afzalipour Hospital, Kerman, Iran - Rohaneh Rahimisadegh; Mohsen Aminizadeh; Moghaddameh Mirzaee; Mohammad Reza Amiresmaili (Kerman University of Medical Sciences, 2018)
Background Training of human resources, especially nurses, is a profitable investment for hospitals with major economic return if properly planned and implemented. Objectives The present study aimed to evaluate the effectiveness of a cardiopulmonary resuscitation (CPR) course as an in-service training program, based on the Kirkpatrick model. Methods This interventional study was conducted at Afzalipour Hospital of Kerman, Iran from October 2014 to May 2015. The study sample consisted of 45 nurses, including 20 nurses in the case group and 25 nurses in the control group. The case group participated in a four-hour CPR training workshop. The Kirkpatrick model was used to determine the effectiveness of the CPR course. Data were collected using three questionnaires and hospital records. Results The participants were satisfied with the training course, and a significant difference was observed in the mean score of three intervals of learning levels evaluation (P < 0.0001). Based on the findings, CPR training affected the learning level of nurses from the case group; however, the average learning score was not significantly different between the two groups (P = 0.26). In addition, the difference in the mean score of behavior level was not significant before and after training (P = 0.91). The results of Chi-square test also showed that CPR training did not affect the forth level (P = 0.54). Finally, the overall effectiveness of the CPR training course was estimated at 32.51%. Conclusions This study indicated that effectiveness of in-service training is not at a desirable level. Since organizations allocate a lot of their resources to such training courses every year, it is essential to reconsider planning and implementation processes.